2016
DOI: 10.1182/blood.v128.22.4500.4500
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Cyclophosphamide and Higher Doses of Dexamethasone Do Not Improve Outcomes of Patients with AL Amyloidosis Treated with Bortezomib

Abstract: Treatment of AL amyloidosis is based on the elimination of the plasma cell clone that produces the amyloidogenic light chains. Typically, these are indolent clones and plasma cell burden is low, thus, even low dose, low toxicity, regimens may be very effective. Bortezomib is effective in targeting plasma cells. Several series have also shown that bortezomib either as single agent or in combinations, such as bortezomib with dexamethasone (VD) or with the addition of cyclophosphamide (VCD) induce high rates of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Cardiac response was reached in 17% of patients and renal response in 25% of patients 142 . It is not proven that addition of cyclophosphamide to bortezomib‐dexamethasone significantly impacts response or survival 143 . Combinations of novel agents are being reported.…”
Section: Therapymentioning
confidence: 99%
“…Cardiac response was reached in 17% of patients and renal response in 25% of patients 142 . It is not proven that addition of cyclophosphamide to bortezomib‐dexamethasone significantly impacts response or survival 143 . Combinations of novel agents are being reported.…”
Section: Therapymentioning
confidence: 99%
“…This observation is in alignment with a previous analysis from our center showing that the addition of cyclophosphamide to bortezomib/dexamethasone may offer some additional efficacy, but this benefit is not substantial. 8 Taken together, these data indicate that while bortezomib is probably the most effective single drug in patients with AL amyloidosis, the optimal partner has not been defined. In this regard, the addition of daratumumab (or another anti-CD38 antibody) or another targeted therapy (such as venetoclax in patients with t (11;14)) may offer a new opportunity to improve significantly over current bortezomib combinations and is under investigation in a large randomized study (NCT03201965).…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] The declaration of complete response (CR) required a normal free light chain (FLC) ratio and a negative immunofixation in at least 2 consecutive measurements. A rigorous assessment protocol following our standard institutional protocol for efficacy and toxicity 8,26,[33][34][35] is followed for all patients treated for AL amyloidosis, including monthly assessment of hematologic and organ response, during the course of active therapy. Toxicity grading is following Common Terminology Criteria for Adverse Events version 4.03 criteria, according to our institution's policy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] A European study showed that the addition of cyclophosphamide to the BDex regimen had no signi cant impact on e cacy. 14 Considering the high activity of bortezomib on plasma cells and the low tumor burden of AL amyloidosis, BDex regimen was recommended for treating newly diagnosed patients not eligible for transplant in Mayo Strati cation of Myeloma and Risk-Adapted Therapy (mSMART) Consensus Statement published in 2015. 15 Studies conducted in the United Kingdom showed high clonal response rates using cyclophosphamide, thalidomide and dexamethasone (CTD), and this treatment has been used for rst-line therapy for AL amyloidosis over the last decade in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%